Innovation through the Quintuple Helix in living labs: lessons learned for a transformation from lab to ecosystem - Merino-Barbancho, Beatriz; Abril Jiménez, Patricia; Mallo, Irene; Lombroni, Ivana; Cea, Gloria; López Nebreda, Cristina; Cabrera, María Fernanda; Fico, Giuseppe; Arredondo, María Teresa (Frontiers in Public Health, 2023)
This is a provisional file, not the final typeset article initial design phases and entry point for newcomers to the process, 2) THE CLUB: Controlled interaction environment where returning users validate solutions, focusing mainly on AHA services (MAHA CLUB), such as exergames, social interaction applications, brain training activities, etc. 3) THE NEIGHBOURHOOD: Real-life environments for free and open interaction between actors and implementation of previously validated and tested solutions.The Quintuple Helix model applied in LifeSpace's new vision allows a coordinated involvement of a more diverse set of actors, beyond the end-users and especially those who are not traditionally part of research and innovation processes.